The use of scanning electron microscopy and energy dispersive X-ray spectroscopy in a case of occupational death. (September 2020) - Aquila, I; Boca, S; Ricci, P; Perozziello, G; Candeloro, P; Di Fabrizio, E; Malara, N; Gratteri, S; Sacco, MA; Francardi, M
Scanning electron microscopy is a technique that provides high-resolution images at the micro- and nano-scale. The combination of scanning electron microscopy and energy dispersive X-ray spectroscopy analysis is developing fast for application in forensic science. In this work, we report a case of work-related traumatic death of a 50-year-old man. The autopsy showed cranial fractures with cerebral haemorrhage. It was more difficult to understand the accident dynamics because the body had been shifted from the accident site to mask what had really taken place. Scanning electron microscopy/energy dispersive X-ray spectroscopy was used to identify the material of the impacting tool and to establish the possible legal responsibility of the employer. In this study, we demonstrate that scanning electron microscopy/energy dispersive X-ray spectroscopy is a useful forensic tool for the analysis of biological samples. Further, for studying the lacerations on the corpse from doubtful blunt tools, scanning electron microscopy/energy dispersive X-ray spectroscopy can assist in demonstrating that the scene has been falsified, as it was in this case.